Pengaruh Pengawasan Terhadap Kinerja Melalui Disiplin Kerja Pada Kantor Camat Rantau Kopar Kabupaten Rokan Hilir - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This study aims to determine the direct and indirect effects of supervision variables on employee performance through work discipline. The data sources obtained are secondary data. While the data analysis technique is Path analysis using a structural model to test the direct and indirect relationships between variables, the tool used is SPSS 25. The results of the study indicate that direct supervision has an effect on employee performance, while indirect supervision through work discipline does not have a significant effect on employee performance. And the results of the supervision variables directly affect employee work discipline